Icarisid II inhibits the proliferation of human osteosarcoma cells by inducing apoptosis and cell cycle arrest - Yuanyuan Tang; Mao Xie; Neng Jiang; Feifei Huang; Xiao Zhang; Ruishan Li; Jingjing Lu; Shijie Liao; Yun Liu (Tumor Biology)
Icarisid II, one of the main active components of Herba Epimedii extracts, shows potent antitumor activity in various cancer cell lines, including osteosarcoma cells. However, the anticancer mechanism of icarisid II against osteosarcoma U2OS needs further exploration. This study aims to investigate further antitumor effects of icarisid II on human osteosarcoma cells and elucidate the underlying mechanism. We cultivated human osteosarcoma USO2 cells in vitro using different concentrations of icarisid II (0–30 µM). Cell viability was detected at 24, 48, and 72 h using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide analysis. Cell cycle was tested by flow cytometry after treatment with icarisid II for 48 h. Annexin V–allophycocyanin and 7-aminoactinomycin D staining were conducted to detect cell apoptosis. Quantitative real-time polymerase chain reaction and Western blot assay were performed to measure the levels of genes and proteins related to cell cycle and apoptosis. Results showed that icarisid II significantly inhibited the proliferation and induced apoptosis of human osteosarcoma U2OS cells. The half maximal inhibitory concentration values were 14.44, 11.02, and 7.37 µM at 24, 48, and 72 h, respectively. Cell cycle was arrested in the G2/M phase in vitro. In addition, icarisid II upregulated the expression levels of P21 and CyclinB1 whereas downregulated the expression levels of CyclinD1, CDC2, and P-Cdc25C, which were related to cell cycle arrest in U2OS cells. The cell apoptotic rate increased in a dose-dependent manner after treatment with icarisid II for 48 h. Icarisid II induced apoptosis by upregulating Bax, downregulating Bcl-2, and activating apoptosis-related proteins, including cleaved caspase-3, caspase-7, caspase-9, and poly (ADP-ribose) polymerase. These data indicate that icarisid II exhibits an antiproliferation effect on human osteosarcoma cells and induces apoptosis by activating the caspase family in a time- and dose-dependent manner in vitro. Therefore, icarisid II may be used as a candidate agent for the clinical treatment of osteosarcoma in the future.